2019
DOI: 10.1002/lno.11121
|View full text |Cite
|
Sign up to set email alerts
|

Estimating lake–climate responses from sparse data: An application to high elevation lakes

Abstract: Although many studies demonstrate lake warming, few document trends from lakes with sparse data. Diel and seasonal variability of surface temperatures limit conventional trend analyses to datasets with frequent repeated observations. Thus, remote lakes, including many high elevation lakes, are underrepresented in trend analyses. We used a Bayesian technique to analyze sparse data that explicitly incorporated diel and seasonal variability. This approach allowed us to estimate lake warming in a region of limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 85 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…Climate change has many negative consequences on lake ecosystems (Adrian et al, 2009), with lakes warming often at rates steeper than air temperature (Ptak et al, 2018; Richardson, Melles, et al, 2017), and decreasing hypolimnetic dissolved oxygen (Couture et al, 2015; Foley et al, 2012; Rösner et al, 2012). Extreme events can exacerbate these changes (Jennings et al, 2012; Zwart et al, 2017), while hydrology and topography can mitigate some of these aspects, especially in mountain systems (Christianson et al, 2019; Šporka et al, 2006), at least temporarily. For example, ice phenology is strongly dependent on direct solar radiation and less so on air temperature (Novikmec et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change has many negative consequences on lake ecosystems (Adrian et al, 2009), with lakes warming often at rates steeper than air temperature (Ptak et al, 2018; Richardson, Melles, et al, 2017), and decreasing hypolimnetic dissolved oxygen (Couture et al, 2015; Foley et al, 2012; Rösner et al, 2012). Extreme events can exacerbate these changes (Jennings et al, 2012; Zwart et al, 2017), while hydrology and topography can mitigate some of these aspects, especially in mountain systems (Christianson et al, 2019; Šporka et al, 2006), at least temporarily. For example, ice phenology is strongly dependent on direct solar radiation and less so on air temperature (Novikmec et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As we seek to predict how the ecological stoichiometry of cryosphere-influenced headwater lakes and streams will change, additional factors must be considered. First, even though atmospheric temperatures are rising more quickly at high elevations than almost anywhere on Earth (Nogués-Bravo et al, 2007), mountain lakes may actually be warming more slowly than those in low elevations (Christianson et al, 2019). The same is likely also true for headwater streams.…”
Section: Climate Change Implicationsmentioning
confidence: 99%
“…where DD is cumulative degree days, N is the number of days in the simulation, T daily are daily average simulated temperatures, and T base is baseline temperature. We used T base = 4°C because this temperature represents the minimum temperature for growth of salmonids (Piper et al 1982;Wedemeyer 2001;Roberts et al 2017;Christianson et al 2019). The number of days in simulations differed because starting dates varied with snowmelt date.…”
Section: Thermodynamic Modelingmentioning
confidence: 99%
“…Many studies have demonstrated that worldwide lakes are becoming warmer and more strongly stratified (Adrian et al 2009;Kirillin 2010;Schmid, Hunziker, and Wüest 2014;O'Reilly et al 2015;Michelutti et al 2016;Christianson et al 2019;Christianson, Johnson, and Hooten 2020). These changes to lake thermal regimes have important implications for lentic ecosystem structure and function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation